Exploring the impact of nonylphenol exposure on Litopenaeus vannamei at the histological and molecular levels - Xianbin Su; Teng Li; Xiaowen Zhu; Peihua Zheng; Huakang Pan; Hui Guo (Ecotoxicology and Environmental Safety, 2024)
Nonylphenol (NP) is one of the common pollutants in the environment that have toxic effects on aquatic animals. Nevertheless, little is known about the possible toxicity mechanism of NP on the hepatopancreas of Litopenaeus vannamei. In the present study, the detrimental effects of NP on the hepatopancreas of the L. vannamei were explored at the histological and transcriptomic levels. The findings indicated that after NP exposed for 3, 12, and 48 h, the hepatopancreas histology was changed significantly. Transcriptomic analysis showed that a total of 4302, 3651, and 4830 differentially expressed genes (DEGs) were identified at 3, 12, and 48 h following NP exposure. All these DEGs were classified into 12 clusters according to the expression patterns at different time points. GO and KEGG enrichment analyses of DEGs were also performed, immunological, metabolic, and inflammatory related pathways, including arachidonic acid metabolism (ko00590), the PPAR signaling pathway (ko03320), and the regulation of TRP channels by inflammatory mediators (ko04750) were significantly enriched. Six DEGs were selected for validation by quantitative real-time PCR (qRT-PCR) and the results confirmed the reliability of transcriptome data. All results indicated that NP is toxic to L. vannamei by damaging the histopathological structure and disrupting the biological function. The findings would provide a theoretical framework for lowering or limiting the detrimental impacts of NP on aquaculture and help us to further study the molecular toxicity of NP in crustaceans.